Metode Tahlili Dalam Penafsiran Al-Qur’an: Anilisis Terhadap Karya - karya Tafsir dan Relevansinya Untuk Pengembangan Studi al-Qur’an di Indonesia - Zaman, Komaru (Indonesian Journal of Humanities and Social Sciences, 2023)
Interpretation of the Qur’an is a scientific study that requires the observer’s thinking power, using various methods for comprehensive understanding. The tahlili method aims to interpret the Qur’an as a whole, starting from surah al-Fatihah to al-Nas, including aspects such as vocabulary (mufradat), reasons for the revelation of verses (sabab al-nuzul), correlation (munasabah), and contextualization of verses so that they can be used as references in studying the Koran. To understand the implementation of the tahlili method, this research uses a library study approach, collecting data from library sources such as books, magazines and documents related to tahlili interpretation. Through this exploration, the author is interested in the tafsir books that have been written by mufassir in Indonesia, while several tafsir books that use the tahlili method have been identified, including "Tafsir Al-Qur’an Al-Karim" by Mahmud Yunus, "Tafsir al-Karim" Hidayah Persis," "Tafsir al-Azhar" by HAMKA, "Tafsir Al-Qur’an Al-Majid," "Tafsir al-Bayan" by T.M. Hasbi ash-Shidieqy, and "Tafsir Rahmat" by Oemar Bakry, as well as "Tafsir al-Misbah" by M. Quraish. The existence of these works should be a motivation for current Al-Qur’an researchers to be able to produce tahlili tafsir books, so that studies or interpretations can be more optimal in contributing to the progress of Al-Qur’an studies and ensuring better understanding and relevance. to the holy text of the Qur’an.